Pengaruh Komisaris Independen, Intellectual Capital, Pertumbuhan Penjualan, dan Umur Perusahaan Terhadap Kinerja Keuangan - Qonita, Alya; Zanaria, Yulita; Sari, Gustin Padwa (Universitas Muhammadiyah Metro, 2023)
This study aims to analyze Independent Commissioners, Intellectual Capital, Sales Sales and Company Age on Financial Performance. This type of research is quantitative, in this study researchers used secondary data through financial reports on companies with a population of 80 companies. The sampling technique used purposive sampling with several criteria so that 73 companies were obtained. Data analysis in this study used the multiple linear regression analysis test method. The results of this study indicate that the Independent Commissioner has a negative effect on Financial Performance, Intellectual Capital has a positive effect on Financial Performance, Sales Growth has a positive effect on Financial Performance, and Company Age has a positive effect on Financial Performance